Overview on Selective Encryption of Image and Video: Challenges and Perspectives. (28th December 2008) - Massoudi Massoudi, A. A.; Lefebvre Lefebvre, F. F.; De Vleeschouwer De Vleeschouwer, C. C.; Macq Macq, B. B.; Quisquater Quisquater, J.-J. J.-J.
Abstract : In traditional image and video content protection schemes, called fully layered, the whole content is first compressed. Then, the compressed bitstream is entirely encrypted using a standard cipher (DES, AES, IDEA, etc.). The specific characteristics of this kind of data (high-transmission rate with limited bandwidth) make standard encryption algorithms inadequate. Another limitation of fully layered systems consists of altering the whole bitstream syntax which may disable some codec functionalities. Selective encryption is a new trend in image and video content protection. It consists of encrypting only a subset of the data. The aim of selective encryption is to reduce the amount of data to encrypt while preserving a sufficient level of security. This computation saving is very desirable especially in constrained communications (real-time networking, high-definition delivery, and mobile communications with limited computational power devices). In addition, selective encryption allows preserving some codec functionalities such as scalability. This tutorial is intended to give an overview on selective encryption algorithms. The theoretical background of selective encryption, potential applications, challenges, and perspectives is presented.